MODEL PENGAJARAN TANPA TUJUAN [ NON DIRECTIVE ] DALAM PEMBELAJARAN DI SEKOLAH DASAR PRINSIP, KARAKTER, DAN IMPLIKASINYA TERHADAP PENGEMBANGAN DIRI SISWA - EUIS WIDYANINGRUM (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
This study examines the implementation of the Non-Directive Teaching Model within the context of elementary education, a level of schooling traditionally dominated by authoritarian instructional approaches and the pursuit of rigid competency-based curricular targets. The Non-Directive Model, rooted in Carl Rogers' humanistic psychological theory, prioritizes students' personal and emotional growth over mere cognitive transfer. The discussion in this article highlights a fundamental shift in the teacher's role from an "instructor" to a "facilitator" who provides space for students to explore their interests without the pressure of externally imposed goals. Furthermore, this article provides an in-depth analysis of the model's operational mechanisms, which encompass five main phases: defining the situation, exploring the problem, developing insight, self-directed action planning, and integration of learning outcomes. The focus of the discussion is directed toward how the absence of "fixed instructional objectives" at the beginning of the session actually triggers students' intrinsic motivation to authentically establish their own learning goals. An analysis was conducted on the impact of this model on classroom dynamics in elementary schools, revealing that despite challenges in time management and teacher mental preparedness, this approach significantly reduces learning anxiety and enhances children's metacognitive abilities. The results of the study conclude that non-directive teaching is effective in shaping independent, creative student characters with high self-awareness. This model offers a solution for modern elementary education to transition from standardization toward personalization, where the meaning of learning is discovered through open dialogue and unconditional positive regard within the classroom ecosystem.